2019
DOI: 10.1371/journal.pmed.1002920
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors for child development: An observational South African birth cohort

Abstract: BackgroundApproximately 250 million (43%) children under the age of 5 years in low- and middle-income countries (LMICs) are failing to meet their developmental potential. Risk factors are recognised to contribute to this loss of human potential. Expanding understanding of the risks that lead to poor outcomes and which protective factors contribute to resilience in children may be critical to improving disparities.Methods and findingsThe Drakenstein Child Health Study is a population-based birth cohort in the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
1
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 104 publications
(132 citation statements)
references
References 48 publications
3
117
1
11
Order By: Relevance
“…This suggests that the cognitive development and communication of LBW babies in Haitian society are delayed. This is not unexpected and has been well described in other studies [33]. One unexpected finding from this study was that male babies had consistently higher estimates for weight, length, cognitive skills and communication skills in both the NBW and LBW groups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This suggests that the cognitive development and communication of LBW babies in Haitian society are delayed. This is not unexpected and has been well described in other studies [33]. One unexpected finding from this study was that male babies had consistently higher estimates for weight, length, cognitive skills and communication skills in both the NBW and LBW groups.…”
Section: Discussionsupporting
confidence: 91%
“…Of the infants enrolled, more LBW infants were female compared to NBW infants (58.4% vs. 42.4%) ( Table 1). The mean gestational age in LBW babies was approximately five weeks shorter than in NBW babies (LBW: 35 weeks [IQR: [32][33][34][35][36][37][38][39], NBW: 40 weeks [39][40]; p < 0.001). According to the prematurity categories, 16 NBW babies (8.2%) were born with late or moderate prematurity (32 to 36 weeks gestational age) ( Table 1).…”
Section: Description Of Study Participantsmentioning
confidence: 99%
“…We found that children of mothers with higher SES were less likely to experience neurodevelopment delay in these domains; higher SES may provide a healthy and stimulating home environment, with positive impact on child neurodevelopment [34][35][36][37]. Other African studies also report higher maternal SES to be positively associated with child gross-fine motor neurodevelopment [38,39], which may be partly due to educated mothers being knowledgeable about the importance of providing stimulating environment for their children, and those employed able to afford physically-stimulating learning activities. Higher maternal SES may mediate child neurodevelopment through improved child nutrition [39].…”
Section: Discussionmentioning
confidence: 92%
“…Several maternal protective and risk factors were associated with cognitive and motor developmental outcomes. For example, maternal education and SES were shown to be protective factors whereas maternal anaemia in pregnancy, depression, partner violence and HIV infection were shown to be risk factors ( 41 ) . Maternal weight and diet also influenced neurobehavioural and motor performance at birth and at 6 months.…”
Section: Resultsmentioning
confidence: 99%